(untitled) (Global Journal of Human-Social Science, 2012)
The purpose of this experiment was to investigate the effects of innovative teaching strategies on the performance of students of grade 1 The experiment was done on the teaching of science subject to the students of grade 1 A sample of 50 students boys and girls was selected randomlyout of the population of 100 students in grade 1 from anEnglish medium school of Islamabad Two groups of 25 students each were made Pre-test of General Science was given to both the groups and the results were recorded One group was taken as a control group which was taught science by the teacher who used conventional method of teaching while the other i e the experimental group was taught by the teacher who used innovative teaching techniques After one month s time of teaching a post-test was conducted